The relationship between dyadic coping and dyadic adjustment among HIV-serodiscordant couples - Martins, Alexandra (2021)
Living within an HIV-serodiscordant relationship has been recognized as a stressful experience for both HIV-infected and HIV-uninfected partners. However, no study has examined the association between dyadic coping (DC) and dyadic adjustment of such couples. In this study, we analysed the association between DC (positive, negative, and common DC) and dyadic adjustment (consensus, satisfaction, cohesion) among HIV-serodiscordant couples, considering individual and cross-partner effects. This cross-sectional study included a sample of 44 HIV-serodiscordant different-sex couples, in a relationship for an average of 16.46 years. The self-reported measures included the Dyadic Coping Inventory and the Revised Dyadic Adjustment Scale. For HIV-infected partners, their own common DC was significantly associated with cohesion, and a cross-partner effect of common DC on satisfaction was found. For HIV-uninfected partners, individual effects of common DC on all dyadic adjustment subscales and a cross-partner effect of common DC on cohesion were found. Additionally, their own and their HIV-infected partners' negative DC were significantly associated with cohesion and satisfaction, respectively. These findings suggest that the perception of common DC has a particularly important role in explaining the different components of dyadic adjustment of both partners facing HIV-serodiscordancy, whereas negative DC is linked to the adjustment of HIV-uninfected partners.